2018
DOI: 10.1159/000492754
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Training After Pulmonary Endarterectomy for Patients with Chronic Thromboembolic Pulmonary Hypertension

Abstract: Background: After undergoing a procedure of pulmonary endarterectomy (PEA), patients with chronic thromboembolic pulmonary hypertension (CTEPH) may still experience reduced exercise capacity. Data on effects of exercise training in these patients are scant. Objectives: To evaluate the effectiveness of exercise training after PEA for CTEPH and if the presence of “residual pulmonary hypertension” may affect the outcome. Methods: Retrospective data analysis of CTEPH patients undergoing inpatient exercise training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 35 publications
0
23
0
1
Order By: Relevance
“…In Nicolino Ambrosino's study ( 21 ), CTEPH patients were divided into Group 1 ( n = 84) and Group 2 ( n = 26) according to the post-surgery hemodynamic response. Group 1 patients met at least one of the following criteria: (1) mPAP ≤ 25 mm Hg; (2) ≥50% reduction in mPAP; and (3) ≥70% reduction in PVR.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Nicolino Ambrosino's study ( 21 ), CTEPH patients were divided into Group 1 ( n = 84) and Group 2 ( n = 26) according to the post-surgery hemodynamic response. Group 1 patients met at least one of the following criteria: (1) mPAP ≤ 25 mm Hg; (2) ≥50% reduction in mPAP; and (3) ≥70% reduction in PVR.…”
Section: Resultsmentioning
confidence: 99%
“…We retrieved 73 articles for more detailed analysis after 68 initial articles were identified by the search and included 4 studies in our systematic review (Figure 1). There were four prepost interventional studies, encompassing 208 exercise-training participants between 2012 and 2020 (17,(21)(22)(23). All studies used a supervised exercise training programme combined with aerobic exercise (treadmill or bicycle Ergometer) and resistance training.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In several studies major improvements in echocardiographic parameters within a few days after PEA versus pre-PEA have been reported [18-21]. A recent retrospective analysis of 110 patients with CTEPH after PEA showed a decline of 6MWD after PEA, which was followed by a significant increase after exercise training, and further improvement in exercise capacity after 3 months did not significantly differ between patients with persistent CTEPH and a good haemodynamic response after PEA [22]. Another recent study by Guth et al [23] showed similar improvements mainly using exercise right heart catheterisation to examine patients 1 year after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Zusätzlich ist die Aussagekraft der Ergebnisse durch die geringe Teilnehmerzahl und durch das monozentrische Studiensetting begrenzt. Prinzipiell wurden die positiven Effekte eines gezielten körperlichen Trainings bei CTEPH-Patienten aber bereits auch schon in früheren Studien gezeigt [3, 4]. Die vorliegende Arbeit ergänzt diese Ergebnisse um weitere Aspekte: Der frühzeitigere Einsatz eines körperlichen Trainingsprogramms scheint sinnvoller zu sein und die Fortführung des körperlichen Trainings im häuslichen Rahmen erbrachte weitere Verbesserungen in Hämodynamik und körperlicher Leistungsfähigkeit.…”
Section: Transfer In Die Praxis Von Magdalena Schmidt (Wald) Und Pd Dunclassified